Brand equity and purchase intention of male branded cosmetic products / Nurul Filza Irdina Johari - Johari, Nurul Filza Irdina (Faculty of Business and Mangement, 2018)
The cosmetic industry is one of the fastest industry that rapidly grow and profitable for the country. There are few studies within male branded cosmetic products since people always thought cosmetic is related to make-up. However, this study is emphasized on male branded cosmetic products. The purpose of this research to study brand equity and purchase intention of male branded cosmetics. The study measures the equity of the brand and identifies the impact of brand equity on purchase intentions. There are four variables for this study, which are brand awareness, brand association, brand loyalty and perceived quality. This study is focused on male consumer in Nilai and Bangi. There are 126 questionnaires has been distributed. The results from this study shows brand awareness is giving the most impact towards purchase intention. Besides that, this study has used convenience sampling to distribute the questionnaires. This study also used SPSS to get correlation and regression data.